2018
DOI: 10.5137/1019-5149.jtn.23279-18.1
|View full text |Cite
|
Sign up to set email alerts
|

Television tip-over related head injuries: a particular type of child neglect

Abstract: cases (8). The majority of the parents of children suffering a TV tip-over-related injury are unaware that this kind of event poses a significant risk for their children (19). The purpose of this study was to identify, report, and raise awareness of the risk factors for TV tip-over. █ MATERIAL and METHODS In total, 86 children who were brought to the emergency department and hospitalized in the neurosurgery clinic of our hospital because of TV tip-over-related head trauma between August 2011 and August 2016 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…In this study, most skull fractures were localised to the occipital bones 1. This injury pattern may relate to a combination of characteristics in young children including short stature with a large head to body ratio, a thin skull and inadequate reflexive ability to avoid falling objects and cognitive abilities to predict danger 2 5 11. In addition, 25% of young children with head injures from toppling TVs have significant neurological sequalae and functional limitations at discharge from hospital 11 18.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In this study, most skull fractures were localised to the occipital bones 1. This injury pattern may relate to a combination of characteristics in young children including short stature with a large head to body ratio, a thin skull and inadequate reflexive ability to avoid falling objects and cognitive abilities to predict danger 2 5 11. In addition, 25% of young children with head injures from toppling TVs have significant neurological sequalae and functional limitations at discharge from hospital 11 18.…”
Section: Discussionmentioning
confidence: 74%
“…Given the elevation and weight of TVs in relation to young children, injuries from toppling TVs can be severe and potentially fatal, with head and neck injuries commonly being described 2 17. Death from head trauma associated with toppling TVs fluctuates between 2% and 12% 5. We found that children under 6 years are twice as likely to sustain head and neck injuries than older children.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations